Comparison of interradicular distances and cortical bone thickness in two sectors of lower jaw for placement of mini-implants - Aida Nabile Silva Zatarain; Jaime Fabián Gutiérrez Rojo; Sarai Castrejón (Universidad Nacional de Colombia, 2018)
Background: the placement of mini interradicular implants as an alternative for the anchoring of orthodontic appliances varies according to the skeletal classification of Class I or II patients. The correct identification of the root location and cortical thickness as part of the strategic analysis of the area to be intervened is necessary. Objective: to compare tomographically the interradicular distances and thickness of the cortical bone in two sectors of the lower jaw for placement of mini implants. Materials and methods: observational and cross-sectional study that included 120 conical beam CT scans of Class I (60) and Class II (60) skeletal patients. The interradicular distance, buccolingual width and thickness of the buccal cortical bone were measured in three dimensions from the alveolar crest between the second premolar and the first lower right molar and between the canine and the lateral side of the same side. A statistical analysis with a 95% confidence t Student test compared the location of anatomical structures for skeletal class I and II. Results: in the Interradicular Distance, when comparing the values to 95%, between Class I and II, significance was found between canine and right lateral (p = <0.054) at 8 mm. In this same sector, in the buccolingual width, significance was found at the height of 6 mm (p = <. 04). In the thickness of the cortical bone, no statistical differences were found when comparing the values for Class I and II. Conclusions: it is recommended to place mini implants in the two sectors interradicularly at the height of 8 mm in Class I and II. Considering the bucco-lingual width at the height of 6 mm.